Gender Social relations and scientific research at ICSEZ/UFAM (Research, Society and Development, 2023)
Debates about gender inequality are present in several social segments, especially in the university space, in view of this, this study aims to analyze how social gender relations directly impact the scientific production of professors/researchers at ICSEZ/Universidade Federal do Amazonas (UFAM) in Parintins/AM. The research was epistemologically based on historical-dialectical materialism, as a design, a case study was used, with a descriptive, exploratory character and qualitative approaches. As for the participants, there were 12 professors with doctoral degrees, the Administrative Director and the Coordinator of the Scientific Committee of ICSEZ/UFAM. The data collected through the structured interview were systematized and analyzed based on the discourse analysis procedure. In the first part, there was a discussion about the term gender and the importance of this theme in contemporary times. In the second, the participation of women in science and the problematizations about gender differences are historically approached, and finally, the results of the research carried out within the scope of the ICSEZ. It was evident that gender inequality is present in the institution's social relations, especially in the academic productivism of the professors/researchers. Another aspect is the overload of the double working day faced by these women coming from a patriarchal logic, which determines the roles of men and women. Furthermore, it is necessary to provoke and strengthen the debate in order to resolve the inequalities present in the academic space.